2022
DOI: 10.3390/agronomy12040932
|View full text |Cite
|
Sign up to set email alerts
|

Removal of Dominant Species Impairs Nitrogen Utilization in Co-Existing Ledum palustre and Vaccinium uliginosum Communities Subjected to Five-Year Continuous Interruptions

Abstract: Unguided exploitation has impaired the sustainability of natural resources of agronomic non-wood forest plants from understory boglands in boreal forests. The extreme consequences of plant–soil interplay on medicinal plant communities under continuous interruptions need to be understood to implement strategies which can cope with possible ecological degradation. In this study, co-existing Ledum palustre and Vaccinium uliginosum communities were investigated after a four-year interruption of continuous removal … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
2
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

3
3

Authors

Journals

citations
Cited by 6 publications
(3 citation statements)
references
References 68 publications
(99 reference statements)
0
2
0
Order By: Relevance
“…Natural bioactive products extracted from NWFP plants can be not only derived from human/industry-based accesses, but also by nature based solutions [ 13 ]. The management of NWFP plants in original or introduced habitats is a nature-based solution, which endorses a significant yield of bioactive compounds by managing stand attributes [ 11 , 14 , 15 ]. The greenhouse is a combined human/industry- and nature-based solution to culture NWFP plants with all environmental factors controlled [ 16 , 17 , 18 , 19 ].…”
Section: Introductionmentioning
confidence: 99%
“…Natural bioactive products extracted from NWFP plants can be not only derived from human/industry-based accesses, but also by nature based solutions [ 13 ]. The management of NWFP plants in original or introduced habitats is a nature-based solution, which endorses a significant yield of bioactive compounds by managing stand attributes [ 11 , 14 , 15 ]. The greenhouse is a combined human/industry- and nature-based solution to culture NWFP plants with all environmental factors controlled [ 16 , 17 , 18 , 19 ].…”
Section: Introductionmentioning
confidence: 99%
“…In this study, our results showed that Rozellomycota was significantly affected by N addition. Duan et al (2022) found that soil mineral and organic N contents were negatively related to the abundance of Rozellomycota species. Thus, these results suggested that different fungal taxa might have diverse response thresholds to fertilisation among different ecosystems, and their adaptation to N and P additions could depend on the soil nutritional context (Xia et al, 2020).…”
Section: Discussionmentioning
confidence: 99%
“…Similarly, soil TN did not show any increasing trend. These together may be explained by low-elevation conditions benefitting nitrification while run-off impaired nitrate and TN accumulations [45,46]. In contrast, the high-elevation condition did not avail nitrification; hence, TN was accumulated and maintained at a moderate level.…”
Section: N and P Availabilities Along Elevation Gradients For Pinus P...mentioning
confidence: 99%